Evaluasi Kepuasan Pengguna Website mcm.madiunkota.go.id Dalam Updating Data Kemiskinan Menggunakan Analisis SWOT - Hazel Lahfahukama Masruri; Mei Lenawati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to evaluate user satisfaction with the website mcm.madiunkota.go.id as a tool for updating poverty data in Madiun City. The website is utilized by the Regional Development Planning Agency (BAPPEDA) as a data management platform to support regional development planning. This research applies a quantitative descriptive approach with data collection methods including observation, interviews, and questionnaires using a Likert scale. The results indicate that users are generally satisfied with the system, particularly in terms of ease of use and feature completeness. However, several issues were identified, such as system errors, data loss after input processes, and limited user capability in operating the system. Based on the SWOT analysis, the system has strong potential for development, but requires improvements in system reliability, data security, and user capacity. This study is expected to provide recommendations for developing more effective, efficient, and sustainable web-based information systems in managing poverty data.